The Relationship of Patient Assessment of the Implementation of Nurse Therapeutic Communication with Patient Satisfaction with Service - Hillary Agustin Dahur; Ari Rahmat Aziz; Anisa Yulvi Azni (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
Therapeutic communication is a crucial aspect of nursing care that reflects the interpersonal skills of nurses in establishing a professional, empathetic, and attentive relationship with patients. In the context of holistic care, therapeutic communication significantly influences patients' perceptions and experiences regarding the quality of healthcare services they receive. This study aims to analyze the relationship between patients' assessments of nurses' therapeutic communication and their satisfaction with inpatient services. The study employed a quantitative method with a descriptive correlational design. A total of 234 patients were selected using purposive sampling, with inclusion criteria of patients who could communicate effectively (without hearing or speech impairments) and exclusion criteria of patients in critical conditions or those discharged against medical advice. The instrument used to assess nurses' therapeutic communication demonstrated validity ranging from 0.517 to 0.855 and reliability with a Cronbach alpha value of 0.962. Data were analyzed using the Pearson Chi-Square statistical test. The univariate analysis showed that 56% of patients rated nurses' therapeutic communication as good, while 73.1% expressed satisfaction with the services. The bivariate analysis yielded a p-value of 0.001 (p < 0.05), indicating a significant relationship between the assessment of therapeutic communication and patient satisfaction.